Qualitative detection of muramic acid in normal mammalian tissues. - Sen, Z (Infect Immun, 1984)
Rat tissues were extracted with 8% trichloroacetic acid, and the products were hydrolyzed with hydrochloric acid and purified. Fluorescamine derivatives were made and subjected to thin-layer chromatography; material with an Rf corresponding to the authentic muramyl derivative was obtained. It was oxidized with periodate, and the resulting formaldehyde was identified fluorimetrically. Alternatively, treatment with base released D-lactate (beta-elimination), which was identified fluorimetrically by reduction of NAD to NADH with D-lactate dehydrogenase. The data indicate that small muramyl compounds, presumably peptides of bacterial origin, are normally present in rat liver, brain, and kidney. The functions of muramyl compounds are suggested by much recent work.